2017
DOI: 10.5539/ijbm.v12n8p80
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-country Study of the Effects of Institutional Ownership on Credit Ratings

Abstract: A considerable number of studies have examined the relationship between corporate governance (CG) structures and corporate performance (e.g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Board From a productivity point of view, it is assumed that board efficiency can have significant improvements when the board members are of different genders (Carter et al, 2010). In terms of legitimacy, boards with the highest gender diversity enable more stable macro-environmental links for companies and stakeholders, and increase the legitimacy of the company and the credibility of the board (AlHares & Ntim, 2017). Several studies have shown that board diversity has a positive effect on the voluntary application of corporate governance principles, which has not been examined in any study yet for the Kosovo case.…”
Section: Board Diversitymentioning
confidence: 99%
“…Board From a productivity point of view, it is assumed that board efficiency can have significant improvements when the board members are of different genders (Carter et al, 2010). In terms of legitimacy, boards with the highest gender diversity enable more stable macro-environmental links for companies and stakeholders, and increase the legitimacy of the company and the credibility of the board (AlHares & Ntim, 2017). Several studies have shown that board diversity has a positive effect on the voluntary application of corporate governance principles, which has not been examined in any study yet for the Kosovo case.…”
Section: Board Diversitymentioning
confidence: 99%
“…From the legitimation perspective, more diversified boards enable better macroenvironmental links for companies and with influential stakeholders [21] enhancing company legitimacy and the board's trustworthiness [41].…”
Section: Board Diversitymentioning
confidence: 99%
“…Researchers have shown great interest in the subject of corporate governance (CG) and its possible impact on firms. Consequently, several studies have examined the association between (CG) and firm value (AlHares et al, 2018a;Abdelhak et al, 2019;Gompers et al, 2003;Renders et al, 2010;Kumar & Zattoni, 2013); between (CG) and earnings management (Xie, Davidson, & DaDalt, 2003;AlHares, 2020a); between (CG) and compensation (Kaplan, 2012), and between (CG) and voluntary disclosure (Eng & Mak, 2003;AlHares & Ntim, 2017). However, by contrast, studies examining the extent to which institutional ownership drives cost of capital (COC) are rare.…”
Section: Introductionmentioning
confidence: 99%